Clinical significance of CD8+ T cell immunoreceptor with Ig and ITIM domains+ in locally advanced gastric cancer treated with SOX regimen after D2 gastrectomy. (3rd June 2019) - Tang, Weiwei; Pan, Xiongxiong; Han, Di; Rong, Dawei; Zhang, Minghui; Yang, Lulu; Ying, Jie; Guan, Hua; Chen, Ziyi; Wang, Xuehao
ABSTRACT: Gastric cancer (GC) development and progression is significantly associated with tumour immune escape. T cell immunoreceptor with Ig and ITIM domains (TIGIT) inhibits T-cell responses and is associated with human cancers and T cell exhaustion phenotypes, but its role in cancers remains unclear. TIGIT and programmed cell death protein (PD)-1 levels were detected in 441 human GC specimens using histochemistry. We used flow cytometry to evaluate percentage of TIGIT + constituting CD8 + T cells of 23 patients with GC who underwent D2 gastrectomy and the S-1 plus oxaliplatin (SOX) regimen. We investigated the influence of SOX regimen and TIGIT functional antibody on CD8 tumour-infiltrating lymphocytes (TILs). Results showed that PD-1 and TIGIT were significantly over expressed in GC and predicted poorer outcome, agreeing with bioinformatics analysis. Significantly reduced percentages of CD8 + TIGIT + cells were observed in patients after D2 gastrectomy (pre- vs post-surgery, 38 ± 8.7% vs . 26.7% ± 5.2%, p < 0.0001). TIGIT expression on CD8 + T cells was modulated by chemotherapeutics (pre- and post-chemotherapy, 31.3 ± 9% vs. 25.1 ± 4.5%, respectively, p = 0.0047) and higher TIGIT expression in post-chemotherapy group was associated with relapsed GC (p = 0.036). In vitro experiments revealed increased CD8 + TIL proliferation and interferon (IFN)-γ production following SOX regimen and TIGIT functional antibody treatments. In conclusion, TIGIT contributes to CD8 + TILs immune dysfunction in patients with GC. Combination of anti-TIGIT therapy and chemotherapy could be considered a therapy for GC.